ANALISIS VARIASI JUMLAH SUDU TURBIN BERPENAMPANG PELAT DATAR PADA TURBIN AIR ALIRAN VORTEX DENGAN TIPE SALURAN MASUK INVOLUTE - Adnan Al Farisi; Yopi Handoyo; Taufiqur Rokhman (Jurnal Ilmiah Teknik Mesin, 2019)
The One of alternative energy that is environmentally friendly is by untilize water energy and turn it into a Microhydro power plant. Microhydro power plant usually made from utilize the waterfall with the head fell. While utilization for streams with a head small drop is not optimal yet. This is a reference to doing research on harnessing the flow of a river that has a value of head low between 0.7 m – 1.4 m with turning it into a Vortex flow (vortex). The purpose of this research is to know the effect variation number of blade on power and efficiency in the vortex turbine. This research uses experimental methods to find current, voltage, torque and rpm using a reading instrument. The materials research vortex turbine used 6 blade, 8 blade and 10 blade with flat plate. The result showed the highest efficiency is 29,93 % with produce turbine power is 19,58 W, generated on turbine with variation 10 blade with load 3,315 kg and the capacity of water 10,14 l/s. Followed with an efficiency 24,17% and produce turbine power is 15,81 W, generated on turbine with the variation 8 blade with load 3,315 kg and the capacity of water is 10,14 l/s. The the lowest turbine efficiency 22,32% with produce tuebine power 14,60 W, generated on turbine with the variation 6 blade with load 3,315 kg, the capacity of water is 10,14 l/s.